Nusantara Capital City (IKN): Threats and Defense Strategies for Indonesia’s New Capital - Editha Praditya; Firre An Suprapto; Yusuf Ali; Surachman Surjaatmadja; Rui Duarte (The Journal of Indonesia Sustainable Development Planning, 2023)
Jakarta, as the current state capital of Indonesia, plays an important role as the center of government and economy. However, due to several problems in Jakarta, the government has considered relocating the capital city to other regions. The President of Indonesia, Jokowi, has expressed his intention to move the capital city to Kalimantan Island. This relocation has raised concerns about defense policy. This research aims to identify the threats that may arise in the proposed new capital city, Nusantara Capital City (IKN), and to propose strategies to overcome them. The methods used in this research include a qualitative approach based on documented perceptions, assumptions, and judgments among Indonesia’s leaders and a quantitative approach to mapping the comparative postures of relevant defense figures. The results indicate that the highest threat in IKN comes from the air (combat, UAV, ICBM’s), while the low-level threat is the location of IKN, which is near the borders, and FIR coincides with the IASL. The critical aspect of defending IKN would be to strengthen national defense diplomacy in the region. In conclusion, this research provides insight into the potential threats to the proposed new capital city and suggests strategies to mitigate them.